Llegando al fondo de la inversión inmobiliaria: lo nuevo en Fibra y Firbi - Zaldívar Del Águila, Rodrigo; Castillo Vigil, Paola (Pontificia Universidad Católica del Perú, 2017)
FIBRA and FIRBI are newfound investment vehicles in Peru which intend to imitate the form of the USREIT (Real Estate Investment Trusts) establishing a series of benefits to invest in real estate assets. Although the new legislation is ambitious, it is yet perfectible, so that a literal interpretation by the competent authorities (Superintendency of Capital Market– SMV and National Superintendency of Customs and Tax Administration -SUNAT) does not cause such benefits to become unachievable in practice.In the article herein, the authors elaborate an approximation to the FIBRA and FIRBI based on the peruvian regulation, the benefits of the utilization of these mechanisms and the opportunities to improve their regulation.

Los FIBRA Y FIRBI son novedosos vehículos de inversión en el Perú que buscan imitar la forma de los Real Estate Investment Trusts estadounidenses estableciendo una serie de beneficios para invertir en activos inmobiliarios. Si bien la nueva normativa es ambiciosa, esta es aún perfectible, de modo que una interpretación literal por parte de las autoridades competentes (Superintendencia del Mercado de Valores -SMV- y Superintendencia Nacional de Aduanas y Administración Tributaria- SUNAT) no causen que dichos beneficios sean inalcanzables en la práctica.En el presente artículo, los autores elaboran una aproximación a los FIBRA Y FIRBI a partir de la normativa peruana, los beneficios de utilización de dichos mecanismos y oportunidades de mejora en su reglamentación.
Getting real with real estate investment: Recent developments in Fibra and Firbi
Keywords: FIBRA; FIRBI; Superintendencia del mercado de valores; Inversión; Inmuebles; https://purl.org/pe-repo/ocde/ford#5.05.01